Study of hematological parameters in sepsis patients and its prognostic implications - Gupta, Ashish; Gupta, Rahul (International Journal of Research in Medical Sciences, 2019)
Background: Septic response is a leading contributory factor for morbidity and mortality especially in intensive care settings. The current research aims to study the co-relation of various hematological parameters in sepsis patients with the objective to see their effects in prognosis of sepsis patients. Methods: The current study was a cross-sectional study with a sample size of 117 patients with sepsis. Various hematological parameters of all the patients were obtained on day of admission (day 1) and seventh day (day 7) using hemogram reports and the difference of their statistical mean and standard deviation was estimated. Results: There was a significant statistical difference in the mean and standard deviation of neutrophil lymphocyte count ratio (NLCR), red cell distribution width standard deviation (RDW SD), Platelet count (PLT) and Platelet crit (PCT) whereas Mean platelet volume (MPV), Platelet distribution width (PDW) and Platelet large cell ratio (PLCR) showed no significant changes on day 1 and day 7 of observation in patients taken for the study. Conclusions: The prognosis of sepsis can be important when we can clinch the hemogram markers early in the period of sepsis and evaluate them according to the etiology of the respective incidences. Targeted approach can be initiated early in the course of hospitalization and may be a specific index of hemogram could be established to further co relate sepsis and its form in particular diseases.